Bentuk Hukum Pokok-Pokok Haluan Negara - Iskatrinah; Aniek Periani (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2024)
The existence of state direction in the history of the Indonesianconstitutional system has changed. In the Old Order and New Order eras,the role of state policy became very vital as a guide to state development,which at that time, its formal form was called the Outline of State Policy(GBHN). However, after the reform, the existence of state policy was lostas the 1945 Constitution was amended which eliminated the existence ofstate policy in the constitution. State direction is a national developmentconcept that refers to the state's goals to be achieved through a planningsystem that has future projections in order to realize state goals as themain foundation of the state's policy concept.Keywords: Amendments, State Policy, State GoalsAbstrak. Keberadaan haluan negara dalam sejarah sistemketatanegaraan Indonesia mengalami perubahan. Di era Orde Lamadan Orde Baru, haluan negara perannya menjadi sangat vital sebagaipedoman pembangunan negara, yang kala itu, wujud formalnyadisebut sebagai Garis-Garis Besar Haluan Negara (GBHN). Namun,setelah reformasi eksistensi haluan negara menjadi hilang seiringdiamandemen UUD 1945 yang menghilangkan eksistensi haluannegara dalam konstitusi. Haluan negara adalah konsep pembangunannasional yang merujuk pada tujuan negara yang hendak dicapaimelalui sebuah sistem perencanaan yang memiliki proyeksi ke depandalam rangka mewujudkan tujuan negara sebagai fondasi utama darikonsep haluan negara.Kata kunci: Amandemen, Haluan Negara, Tujuan Negara